A Review Study of Nidanarthakara Roga w.s.r. to Sthaulya. - Dhankar, Sanjay; Sharma, Priyanka; Sharma, Manish Kumar; Dudi, Sunita; Kumar, Suresh (International Research Journal of Ayurveda & Yoga, 2023)
Introduction-Ayurveda is a holistic science of life in which many fundamental principles related to Dosha, Dushya, Stotras, Vyadhi utpatti and Vyadhi cikitsa etc. have been described. Ayurveda has presented many aspects related to the prevention of disease and avoidance of diagnosis in the context of Nidana Parivarjan. Diagnosis plays an important role in the manifestation of any disease. Sometimes the disease itself acts as a diagnosis and plays an important role in the onset of another disease. Material & Methods-Material has been collected from Ayurvedic Samhitas, different Research Articles, the internet, etc. Discussion- This concept is explained by Acharya Charaka under the title Nidanarthakar Roga (one disease itself becomes the cause of another disease). In today’s time, it is very important to know the diagnosis of any disease. The present era is more challenging for medical science due to the emergence of various lifestyle diseases. Obesity is also a serious problem related to lifestyle in today’s era. Obesity often serves as a diagnosis for various diseases. Obesity is the cause of high blood pressure, diabetes, infertility, heart disease, some types of fatal diseases.